Pulling the Plug on Clinical Equipoise: A Critique of Miller and Weijer - Gifford, Fred (Kennedy Institute of Ethics journal, 2007)
, As clinicians, researchers, bioethicists, and members of society, we face a number of moral dilemmas concerning randomized clinical trials. How we manage the starting and stopping of such trials—how we conceptualize what evidence is sufficient for these decisions—has implications for both our obligations to trial participants and for the nature and security of the resultant medical knowledge. One view of how this is to be done, "clinical equipoise," recently has been given an extended defense by Paul Miller and Charles Weijer in their article "Rehabilitating Equipoise." The present paper critiques this position and Miller and Weijer's defense of it. I argue that their attempted rehabilitation fails. Their analysis suffers from a number of confusions, as well as a failure to make crucial distinctions, adequately to clarify key concepts, or to think through exactly what needs to be established to justify their claim. We are left with little reason to uphold the clinical equipoise criterion.